2004
DOI: 10.1111/j.0013-9580.2004.16503.x
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence after a First Unprovoked Cryptogenic/Idiopathic Seizure in Children: A Prospective Study from São Paulo, Brazil

Abstract: Summary:Purpose: To evaluate the recurrence risk after a first unprovoked seizure in a large population of children and adolescents of a developing country.Methods: This prospective study was conducted at two tertiary hospitals, between September 1989 and August 1998. Children were enrolled if they had a first unprovoked cryptogenic/idiopathic seizure and maximal interval to the enrollment ≤90 days. EEG and computed tomography (CT) were performed in most patients. Potential predictors of recurrence were compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 21 publications
1
23
2
1
Order By: Relevance
“…In DCs, after a fi rst unprovoked seizure, the risk of recurrence is 33% to 37%, which is similar to that among developed countries [25][26][27]. Studies from DCs show that epilepsy secondary to underlying structural causes [26] or with an abnormal electroencephalogram confers the worst prognosis [27].…”
Section: Prognosismentioning
confidence: 69%
“…In DCs, after a fi rst unprovoked seizure, the risk of recurrence is 33% to 37%, which is similar to that among developed countries [25][26][27]. Studies from DCs show that epilepsy secondary to underlying structural causes [26] or with an abnormal electroencephalogram confers the worst prognosis [27].…”
Section: Prognosismentioning
confidence: 69%
“…the number of seizures before treatment, the total number of seizures, the time period from the initiation of treatment until the convulsions being under control, the duration of discontinuation and seizure relapse rates after AED withdrawal [5,14,22]. It has been reported that the overall seizure relapse rate was 23-71% in patients who did not receive any treatment after the first seizure and seizure relapse rates were higher in patients who had abnormal EEG findings and symptomatic epilepsy [23][24][25][26][27][28]. The relation between age at onset of epilepsy and seizure relapse rates have been investigated in several studies with contradictory results [10,11,29].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of a patient seizures was based on the International League against Epilepsy Classification [8]. A family history of seizures was defined as a history of an unprovoked seizure or seizures in parents or siblings [9]. Serial seizures were defined as multiple seizures within 24 h [10].…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…Persons with status epilepticus or clusters of seizures (two or more) in the same 24-h period were considered to have had a single seizure [15]. Status epilepticus was defined as a seizure lasting N30 min or as a series of seizures, without regaining consciousness between them, lasting N30 min [9]. Patients having three or more seizure episodes were classified as multiple seizure recurrences.…”
Section: Follow-up and Outcome Assessmentmentioning
confidence: 99%